DEVELOPMENT OF MOBILE LEARNING BASED ON AN INTEGRATED PREDICTION GUIDE AS A SUPPORT OF PHYSICS LEARNING IN HIGH SCHOOL ON THE TOPIC OF WAVES - Purwani, Aprilia; Astuti, Irnin Agustina Dwi; Dewati, Maria (UIN Sunan Gunung Djati Bandung, 2022)
This research aimed to develop Android-based Mobile Learning media that is integrated with the Prediction Guide learning model using Smart Apps Creator software as research supporting high school physics learning on wave material. The research method used in this research is Research and Development (R &D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). However, due to the condition of the Covid-19 pandemic, this development research is only carried out until the development stage. The techniques used in analyzing data are descriptive analysis techniques by calculating the percentage of expert validation scores and student response tests. The analysis of this study obtained an average of 83% from media experts, 89% from material experts, and 86% from linguists. Thus, the overall average percentage of expert validation obtained an average percentage value of 86%, with very feasible information, and can be used in school. Meanwhile, the average percentage obtained from the student response test was 74% which describes a good response from the students.